2008
DOI: 10.1002/pssc.200778500
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of uniform optical properties from microphotoluminescence mapping of InGaN quantum wells grown on slightly misoriented GaN substrates

Abstract: We have studied microphotoluminescence mapping of InGaN quantum wells grown on GaN (0001) substrates with misorientation toward [1$/bar 1$00] direction. The fluctuation of peak energy and full width at half maximum in the mapping was large when the misorientation angle was 0.0° or 0.1°, whereas it was small when the misorientation angle was over 0.2°. The average of the full width at half maximum of InGaN peak had the minimum of below60 meV at room temperature when the misorientation angle was around 0.28°. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Likewise, the FWHM was very uniform for all of the samples, ranging from 11.9 nm for a misorientation angle of À0.061 to 13.5 nm for a misorientation angle of 0.891, corresponding to a linewidth of about 90 meV for the entire range of misorientation angles. These linewidths are comparable to the linewidths of 60-140 meV measured for near-UV InGaN-based thin films and QWs grown on free-standing Ga-polar (0 0 0 1) c-plane GaN substrates [23,24], signifying the relative uniformity of the InGaN-based QWs presented in this study.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Likewise, the FWHM was very uniform for all of the samples, ranging from 11.9 nm for a misorientation angle of À0.061 to 13.5 nm for a misorientation angle of 0.891, corresponding to a linewidth of about 90 meV for the entire range of misorientation angles. These linewidths are comparable to the linewidths of 60-140 meV measured for near-UV InGaN-based thin films and QWs grown on free-standing Ga-polar (0 0 0 1) c-plane GaN substrates [23,24], signifying the relative uniformity of the InGaN-based QWs presented in this study.…”
Section: Resultssupporting
confidence: 80%
“…The authors also determined that an increase in the substrate misorientation resulted in an increase in the PL linewidth and a decrease in the lateral uniformity in the InGaN layers, as revealed by cathodoluminescence (CL) and Z-contrast scanning transmission electron microscopy measurements. In contrast, Tachibana et al [24] found that that the peak PL wavelength of InGaN/ InGaN multiple quantum wells (MQWs) increased slightly with an increase in substrate misorientation toward the [1 0 1 0] m direction on free-standing Ga-polar (0 0 0 1) c-plane GaN substrates. The authors also determined that an increase in the substrate misorientation resulted in a decrease in the PL linewidth and a significant improvement in the lateral spectral uniformity in the InGaN/InGaN MQWs, as revealed by microphotoluminescence (micro-PL) measurements.…”
Section: Introductionmentioning
confidence: 88%
“…[6][7][8][9][10][11][12][13][14] All the experiments described in those references were performed using different homogeneous GaN substrates with different vicinal angles. In this work, we show that the different vicinal angles could be realized within one patterned substrate.…”
mentioning
confidence: 99%
“…Polishing, or cutting under larger angle requires boule-like crystals which are not yet easily available. There is a limited number of papers discussing the growth of InGaN and GaN:Mg on misoriented substrates [3][4][5]. Most of them are related to the structures grown on the sapphire.…”
mentioning
confidence: 99%
“…They observed decrease in the average indium content with the increasing misorientation angle, accompanied by the corresponding increase in the PL energy. Tachibana et al [5] examined the growth of InGaN MQWs (In = 10%) with α between 0 deg and 0.4 deg (GaN substrate). They did not reported a variation of photoluminescence energy with…”
mentioning
confidence: 99%